Pengaruh Media Wayang Gizi Digital terhadap Pengetahuan Gizi Seimbang pada Anak SD N Lempuyangan 1 Yogyakarta - Istu Pambudi, Brevi; Dharma Rini, Afifah (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Fulfillment of energy source needs for the body in elementary school children is greater when compared to toddlers and improving nutritional status can be done by increasing children’s nutritional knowledge. The low knowledge and awareness of parents in providing balanced nutritious food and food for their children greatly affects the low level of balanced nutritional intake in elementary school children. Children’s mindsets can also develop easily if they use puppets as educational media. This study aims to determine the effect of digital nutritional puppet media on balanced nutritional knowledge in elementary school children at Lempuyangan 1 Yogyakarta Elementary School. This study used a quasi-experimental study design with a one group pretest posttest design with a purposive sampling technique. The number of respondents in this study was 53 students. Respondents were given a pretest questionnaire before education and a posttest after being given nutritional education in the form of digital nutritional puppet shows. The results showed that most of the respondents were female (50.9%) with an age of 11 years (56.6%) and most of the duration of playing cellphones> 3 hours/day (47.2%). Based on statistical tests, most respondents experienced an increase in the average value of knowledge about balanced nutrition by 21.1% compared to the pre-test and the Wilcixin test showed that there was an influence of education using digital nutritional puppet media on knowledge of balanced nutrition in elementary school children at Lempuyangan 1 Yogyakarta (p = 0.001). The conclusion of the study is that digital nutritional puppet media can have an effect on increasing knowledge of balanced nutrition in elementary school children.